NUMERICAL SIMULATION OF FLOW PAST TWO CYLINDERS ARRANGED SIDE BY SIDE - Gokul.R,Aby Alias (International Journal of Research Science and Management, 2015)
Pairs of circular cylinders immersed in a cross-flow are encountered in many engineering applications. The cylinders may be arranged in tandem, side-by-side, or staggered configurations. Wake and proximity interference effects, which are determined primarily by the longitudinal and transverse spacing between the cylinders, and also by the Reynolds number, have a strong influence on the flow patterns, aerodynamic forces, vortex shedding, and other parameters. This paper reviews the understanding of the flow around two circular cylinders of equal diameter immersed in a cross-flow at low Reynolds number (Re).